Long‐term corticosteroid use, adrenal insufficiency and the need for steroid‐sparing treatment in adult severe asthma. (1st April 2021) - Gurnell, M.; Heaney, L. G.; Price, D.; Menzies‐Gow, A.
Abstract: Secondary adrenal insufficiency (AI) occurs as the result of any process that disrupts normal hypothalamic and/or anterior pituitary function and causes a decrease in the secretion of steroid hormones from the adrenal cortex. The most common cause of secondary AI is exogenous corticosteroid therapy administered at supraphysiologic dosages for ≥ 1 month. AI caused by oral corticosteroids (OCS) is not well‐recognized or commonly diagnosed but is often associated with reduced well‐being and can be life‐threatening in the event of an adrenal crisis. Corticosteroid use is common in respiratory diseases, and asthma is a representative condition that illustrates the potential challenges and opportunities related to corticosteroid‐sparing therapies. For individuals with severe asthma (approximately 5%–10% of all cases), reduction or elimination of maintenance OCS without loss of control can now be accomplished with biologic therapies targeting inflammatory mediators. However, the optimal strategy to ensure early identification and treatment of AI and safe OCS withdrawal in routine clinical practice remains to be defined. Many studies with biologics have involved short evaluation periods and small sample sizes; in addition, cautious approaches to OCS tapering in studies with a placebo arm, coupled with inconsistent monitoring for AI, have contributed to the lack of clarity. If the goal is to greatly reduce and, where possible, eliminate long‐term OCS use in severe asthma through the increasing adoption of biologic treatments, there is an urgent need for clinical trials that address both the speed of OCS withdrawal and how to monitor for AI. Abstract :